Examining the Psychometric Properties of the Big Three Perfectionism Scale–Short Form (BTPS-SF) among Malaysian Chinese Students at a Private University - Lee, Kam-Fong; Ahadzadeh, Ashraf Sadat; Wu, Shin Ling (Makara Journal of Health Research, 2026)
Background: Perfectionism is increasingly prevalent among young adults and is a significant predictor of pathological and behavioral outcomes. Despite its relevance, validated and reliable measures of perfectionism tailored to university students, particularly within the Malaysian cultural and academic context, are lacking. This study addresses this gap by examining the psychometric properties of the BTPS-SF among Chinese students at a private university in Malaysia. Methods: Data were collected using a cross-sectional design with convenience and snowball sampling from 380 students aged 18–25 years, predominantly from a Chinese student population. Results: The results of the exploratory factor analysis, conducted using principal axis factoring with oblimin rotation, provided preliminary evidence for a three-factor structure of the BTPS-SF—namely, rigid, self-critical, and narcissistic perfectionism—as distinct dimensions. Together, these three factors explained 58.29% of the total variance, with factor loadings ranging from 0.35 to 0.79. Each dimension demonstrated acceptable internal consistency ranging from 0.80 to 0.84, supporting its suitability for use in academic, clinical, and nonclinical settings. Conclusions: This study supports the reliability of the BTPS-SF as a multidimensional measurement tool, demonstrating its efficacy in capturing the three main dimensions of perfectionism: rigid, self-critical, and narcissistic. This facilitates comprehensive analysis and offers a robust foundation for future research on student perfectionism. The study's limitations and recommendations for further research are discussed.